Evolutionary significance of the microbial assemblages of large benthic Foraminifera. (18th November 2018) - Prazeres, Martina; Renema, Willem
ABSTRACT: Large benthic Foraminifera (LBF) are major carbonate producers on coral reefs, and are hosts to a diverse symbiotic microbial community. During warm episodes in the geological past, these reef‐building organisms expanded their geographical ranges as subtropical and tropical belts moved into higher latitudes. During these range‐expansion periods, LBF were the most prolific carbonate producers on reefs, dominating shallow carbonate platforms over reef‐building corals. Even though the fossil and modern distributions of groups of species that harbour different types of symbionts are known, the nature, mechanisms, and factors that influence their occurrence remain elusive. Furthermore, the presence of a diverse and persistent bacterial community has only recently gained attention. We examined recent advances in molecular identification of prokaryotic (i.e. bacteria) and eukaryotic (i.e. microalgae) associates, and palaeoecology, and place the partnership with bacteria and algae in the context of climate change. In critically reviewing the available fossil and modern data on symbiosis, we reveal a crucial role of microalgae in the response of LBF to ocean warming, and their capacity to colonise a variety of habitats, across both latitudes and broad depth ranges. Symbiont identity is a key factor enabling LBF to expand their geographic ranges when the sea‐surface temperature increases. Our analyses showed that over the past 66 million years (My), diatom‐bearing species were dominant in reef environments. The modern record shows that these species display a stable, persistent eukaryotic assemblage across their geographic distribution range, and are less dependent on symbiotic photosynthesis for survival. By contrast, dinoflagellate and chlorophytic species, which show a provincial distribution, tend to have a more flexible eukaryotic community throughout their range. This group is more dependent on their symbionts, and flexibility in their symbiosis is likely to be the driving force behind their evolutionary history, as they form a monophyletic group originating from a rhodophyte‐bearing ancestor. The study of bacterial assemblages, while still in its infancy, is a promising field of study. Bacterial communities are likely to be shaped by the local environment, although a core bacterial microbiome is found in species with global distributions. Cryptic speciation is also an important factor that must be taken into consideration. As global warming intensifies, genetic divergence in hosts in addition to the range of flexibility/specificity within host–symbiont associations will be important elements in the continued evolutionary success of LBF species in a wide range of environments. Based on fossil and modern data, we conclude that the microbiome, which includes both algal and bacterial partners, is a key factor influencing the evolution of LBF. As a result, the microbiome assists LBF in colonising a wide range of habitats, and allowed them to become the most important calcifiers on shallow platforms worldwide during periods of ocean warming in the geologic past. Since LBF are crucial ecosystem engineers and prolific carbonate producers, the microbiome is a critical component that will play a central role in the responses of LBF to a changing ocean, and ultimately in shaping the future of coral reefs.